EKSPRESI PANDANGAN DUNIA KELOMPOK SOSIAL PENGARANG DALAM NOVEL LASKAR PELANGI KARYA ANDREA HIRATA - Herson Kadir (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2013)
This study aims to reveal the author’s social group world view in Andrea Hirata’s novel Laskar Pelangi. It employed the genetic structuralism theory approach. The data were analyzed using a dialectic model through recursive, simultaneous, and iterative understanding of the literary text structure (out of society). The findings show that the cultural issues presented in LaskarPelangi deal with the harmony of the life of the Belitung society consisting of several ethnic groups. The author’s world view is relatedto the importance of social convergence emphasizing a mutual respect attitude towards each ethnic group. Besides, there needs to be an understanding of a local genius value in developing a life norm in a society and a nation.